(untitled) (Research, Society and Development, 2024)
Diabetes Mellitus type 2 (DM2) is characterized by difficulty in adjusting the insulin produced by the pancreas. The increase in risk is mainly related to unhealthy habits and family history, which contrasts with the university lifestyle, driven by high workload, stress and irregular eating. Objective: To carry out an epidemiological analysis of risk factors for the development of DM2 in university students of UFDPAR, correlating lifestyle habits during the COVID-19 pandemic. Methods: Quantitative cross-sectional study, carried out between September 2020 and June 2021 with graduates of the Universidade Federal do Delta do Parnaíba (UFDPar). Results: 252 students who participated in the research observed that overweight and obesity were present in 25.4% of the students, who were not sedentary for the majority in 58.73% of cases. Two risk factors were not avoided, 189 (75%) reported a family history of DM2, with 58 (23.01%) being close relatives (country, family or children). Given that, associated with environmental factors, we increase the risk of adoecimento due to chronic diseases. In relation to lifestyle habits during the isolation period, 30% of students switched to eating more industrialized foods and 58% reported weight gain during the pandemic, while 32% reported eating healthily. Conclusion: Sedentary lifestyle, followed by overweight and inadequate nutrition emerge as the most important factors of predisposition to DM2 in the next 10 years, aggravated in the pandemic period due to years of acquired psychosocial experiences.